(3RgQ GdBOGH hKeQ GdCdHGHs - (3EHQGgje Hf Ydj Hf Jeje GdCfUGQj, CHh ESMGb GdMUQj,J (B453 (3g` s ((3Ydi Hf efUhQ s)
(3ChdgG (B:s
(3eHOY ai TeGFd GdeLO MjKeG CgJOjfG dCNPg hGbJHGSg s
(3BNQgG (B:s
(3bGd eSde Hf bJjHg dGHf YjGT aGfTOg eGdjS dWGYf ajg eWYf (B: (3heG MedJ ef fGbI ahb QMdgG CHQ hGhai Geg ef eMeO ced GdSaQ GdKdfj s
(3fSNI KGdKIs
(3hHChdgG Jedc eDQN ai (B1247(3g` hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B50 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B8s
Keywords: (3GdCOHs